2011
DOI: 10.1111/j.1600-0528.2011.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in oral health from childhood to early adulthood: a life course approach

Abstract: Oral health status had become worse from childhood to early adulthood in the study cohort. Economic circumstance of the subjects was found to be positively related to their utilization of dental services and through this contributed to the subjects' caries experience. Oral health at younger ages was positively associated with succeeding oral health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
69
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 34 publications
6
69
0
2
Order By: Relevance
“…The same appears to be true in Hong Kong, where family income has a direct effect on dental care utilization. 9 The proportion of subjects who had never visited a dentist in each income stratum is more unequal among younger age groups. This is concerning because the major dental diseases, such as caries, begin early in life, affecting the deciduous dentition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same appears to be true in Hong Kong, where family income has a direct effect on dental care utilization. 9 The proportion of subjects who had never visited a dentist in each income stratum is more unequal among younger age groups. This is concerning because the major dental diseases, such as caries, begin early in life, affecting the deciduous dentition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies quantifying inequalities in health care by analyzing access to and utilization of dental care services are becoming increasingly common in the Brazilian 1,2,5 and international 9,18 literature. Hypotheses attempting to explain the positive changes seen in Brazil are complex, and involve socioeconomic and health care-related aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this association was only partly explained upon introduction of control variables for current health and living conditions, including current dental attendance patterns. Because there is evidence on the persistence of dental attendance patterns throughout the life course, 18,36,37 this may suggest that dental attendance in childhood can determine later dental visiting patterns and as such has a cumulative impact on oral well-being throughout the life cycle. In addition, our results coincide with previous studies showing that childhood socioeconomic background influences oral health outcomes in later life years.…”
Section: Discussionmentioning
confidence: 99%
“…12 Evidence from birth-cohort studies on life course determinants of oral health suggests that socioeconomic background, 13---16 dental-attendance patterns in early life years, 17,18 and parental oral health 19,20 play an important role in terms of tooth decay, periodontal health, tooth loss, and self-rated oral health at early adulthood. Moreover, it has been shown that caries experience in early life predicts caries occurrence later in life.…”
mentioning
confidence: 99%
“…19,35 Therefore, it is important for health professionals to know how these chains of risk will cumulatively tend to affect the clinical and psychosocial development of adolescents so that continuous interventions can be planned over their life course to address broader determinants of health. 36 Moreover, research has shown that there are other psychosocial aspects, such as self-esteem, social capital, and sense of coherence associated with behaviors and oral clinical changes. 19,21,37,38 Thus, although these variables were not evaluated herein, they may play a mediating role between caries experience (DMFT index) and changes in OHRQoL over time, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%